ANALISIS GAME GENSHIN IMPACT DALAM MEMBANGUN DAYA TARIK GLOBAL - Situmorang, Michael Immanuel; Sastrawan, I Gede Putu Ryan Andika Hendra; Nugraha, I Nyoman Tri; Putra, Gede Lingga Ananta Kusuma (Pusat Penerbitan LPPM ISI Bali, 2026)
Genshin Impact is a game that has achieved global popularity by leveraging strong animation and visual design. This study aims to analyze the role of animation, story, music and visual design in building the global appeal of Genshin Impact. The research employs a qualitative method with a descriptive analysis approach through visual observation of character animation, environmental visuals, and the overall visual style of the game. Supporting data are obtained from relevant literature on animation, story, music and visual design in the game industry. The results indicate that the application of animation principles, consistent visual style, and detailed, expressive character design play a crucial role in creating an engaging visual experience that is well received by players from diverse cultural backgrounds. Therefore, animation, story, music and visual design are key factors supporting the global success of Genshin Impact.